Laboratory Diagnosis for Giardia Lamblia Infection: A Comparison of Microscopy, Coprodiagnosis and Serology - Marcel A Behr; Evelyne Kokoskin; Theresa W Gyorkos; Lyne Cédilotte; Gaetan M Faubert; J Dick MacLean (Canadian Journal of Infectious Diseases)
OBJECTIVE: To evaluate newer techniques such as coproantigen detection and serology in the diagnosis of symptomatic Giardia lamblia infection.